Mengukur Kesiapan Institusi Riset “Y” dalam Menerapkan SNI ISO 9001:2008 Melalui Iklim Organisasi - Agus Fanar Syukri (STI Policy and Management Journal, 2015)
In the globalization era, consumers are becoming more demanding on the quality of products, including services from public organizations. To improve the quality, many organizations have started to implement a quality management system (QMS) based on SNI ISO 9001:2008. This study determines the perceptions of “Y” organizational readiness in implementing QMS by using Organizational Climate instrument. The number of respondent was 28 out of 32 employees.Data was collected by census, then analyzed by gapmethod.The result showed that Y organization is ready to implement QMS based on ISO 9001, with the smallest gapwas 4.6% for feeling free to talk to superiors about job and the widest gapwas 18% for making decisions level was still on managers,not involving employees yet